Effectiveness of the Prosperous Family Card Program (KKS) in Sanipah Village, Samboja District, Kutai Kartanegara Regency - Afrillia; Muhammad Noor; Muhammad Hairul Saleh (Jurnal Ilmu Pemerintahan, 2021)
This research is intended to find out the implementation of the Prosperous Family Card program in Sanipah Village, Samboja District, Kutai Kartanegara Regency, whether the implementation of the KKS so far has been in accordance with indicators of effectiveness in achieving goals, integration and adaptation. The research location is in the Sanipah Village, Samboja District, Kutai Kartanegara Regency. Data collection was carried out by library research, observation, in-depth interviews, and documentation techniques. Data analysis was carried out by collecting data, condensing data, presenting data, and drawing conclusions or verifying data. The results of this study indicate that the implementation of the Prosperous Family Card Program (KKS) in Sanipah Village, Samboja District is still not effective where the target of KKS recipients is still inaccurate, the distribution time is not consistent, the socialization and communication carried out by the village administration is still lacking so that there are some people who still do not understand its use so that it becomes an obstacle in utilizing assistance, adaptation regarding the use of the Prosperous Family Card is indeed following the times but there are still residents who have problems, especially the elderly regarding saving savings books, their ATM cards and also ATM PINs which are obstacles in receiving benefit.